Compression Performance of Newly Designed Replaceable Tubular Steel Piers - Haifeng Li; Xuehang Zhao; Wei Sun; Zhe Xiong (Advances in Materials Science and Engineering)
To rapidly restore the seismic behaviour of a portal steel bridge column after an earthquake, the installation of replaceable tubular steel piers at the root of a portal steel bridge column is proposed herein. In this study, various tubular steel piers with different structural measures were designed; an axial compression test and a numerical simulation of the newly designed tubular steel piers were performed. The effects of parameters such as the structure of stiffening rib, the strength of LYP steel plate, the size of low-yield-point (LYP) steel plate, and the size of outer constrained steel plate were discussed. The results indicate that local buckling of steel tubular plates is likely to occur at the upper or lower end of those specimens, which belong to type II-A specimens with stiffened LYP steel tubular plates or type III-A specimens with T-shaped LYP steel plates, respectively. This led to the LYP steel plate cannot fully display its function. For type III-B and III-C specimens with embedded LYP steel plates and constrained steel plates on both sides, when the outer steel tubular plates buckle, the internally constrained LYP steel plates provide support for the outer steel tubular plates. The plastic deformation of the specimens is sufficient, and the deformation performance is good. For type IV-A specimens with LYP steel tubular plates and constrained steel plates on both sides, the mechanical behaviour of the new tubular steel piers is significantly improved, and increasing the height of the constrained LYP steel tubular plate can improve the compressive behaviour of the new tubular steel pier. Considering the effect of the steel plate thickness on bearing capacity and deformation performance, the thickness tw of the outer constrained steel plate should be equal to the thickness t of the common steel tubular plate, and the thickness tf of the LYP steel tubular plate should satisfy t ≤ tf ≤ 2t. Finally, a design formula is proposed to calculate the axial bearing capacity of newly designed tubular steel piers with constrained LYP steel plates.